Predictors of Lidcombe Program treatment dropout and outcome for early stuttering. Issue 1 (29th November 2020) - Park, Veronica; Onslow, Mark; Lowe, Robyn; Jones, Mark; O'Brian, Sue; Packman, Ann; Menzies, Ross; Block, Susan; Wilson, Linda; Harrison, Elisabeth; Hewat, Sally
Abstract: Background: Information is available about what predicts Lidcombe Program treatment time, but nothing is known about what predicts treatment prognosis. Aims: To investigate the predictors of treatment dropout and treatment outcome for children who were treated for early stuttering with the Lidcombe Program ( N = 277). Methods & Procedures: A total of 32 variables were used as predictors in regression analyses of short‐ and medium‐term Lidcombe Program outcome, and of treatment dropout. Outcomes & Results: Regression analyses associated children who have better language skills and easy temperament with better treatment outcome, although only a small portion of the variance of treatment outcome was accounted for by these variables. There was an association between treatment dropout and parental scores on a personality screening tool relating to their impulsivity. Conclusions & Implications: Variables identified as predictors of Lidcombe Program treatment outcome were statistically significant, but not clinically significant. They did not account for a clinically substantive portion of treatment outcomes. Findings about parental impulsivity and their relationship with intervention drop‐out require replication with prospective methods and comprehensive assessment of parent psychological status. This is particularly important because parents are involved in conducting all early interventions. What this paper adds: What is already known on the subject: Information is available about what predicts Lidcombe Program treatment time, but nothing is known about what predicts Lidcombe Program treatment outcome. What this paper adds to existing knowledge: There are predictors of Lidcombe Program treatment outcome that are statistically significant, but none are clinically significant. What are the potential or actual clinical implications of this work?: Clinicians can tell parents that nothing has been found that can assist with making prognostic indications about treatment outcome for their children.